Policy spillovers and synergies in a monetary union - Óscar Arce; Samuel Hurtado; Carlos Thomas (European Central Bank (ECB), 2016)
We provide a general equilibrium framework for analyzing the effects of supply and demand side policies, and the potential synergies between them, in an asymmetric monetary union that faces a liquidity trap and a slow deleveraging process in its `periphery`. We find that the joint implementation of pro-competition structural reforms in the periphery, a fiscal expansion in the core, and forward guidance about the future path of nominal interest rates produces positive synergies between the three policies: forward guidance re-inforces the expansionary effects of country-specific policies, and the latter in turn improve the effectiveness of forward guidance. Our results provide a case for complementing current unconventional monetary stimuli in the euro area with national efforts on the structural reform and fiscal fronts.
Keywords: E44; E63; D42; 330; deleveraging; monetary union; structural reforms; synergies; zero lower bound